Considerações acerca do método-clínico terapêutico fonoaudiológico na interface com a psicanálise - Mori, Juliana de Souza Moraes (2011)
INTRODUCTION: From the 90 s, through some theoretical propositions and clinical problems, the Speech Therapy established a dialogue with Psychoanalysis and promoted a rebuilding of its theoretical basis and clinical perspective. AIM: Investigate which contributions Psychoanalysis produces in the Speech Therapy clinical-therapeutic method. METHOD: Quantitative and qualitative research. At first a survey was made in Speech Therapy courses of Brazilian universities in search of teachers/speech pathologists who work with this interface, for which were collected depositions regarding the impact of Psychoanalysis in their clinical therapeutic procedures. The quantitative data that was obtained composed a map that was structured in tables wich was submitted to a statistical examination that expose the interface between Speech Therapy and Psychoanalysis into the studied context. Concerning qualitative data extracted from the depositions, were organized according to categorical analysis proposed by Bardin (2002). For the analysis, it was used an extract from the clinic via therapist-patient relationship and the discussion was circumscribed and privileged by the Speech Therapy literature sustained by an articulation with Psychoanalysis and the psychoanalytic texts about the subject, symptom and transfer. RESULTS: The quantitative results shown that such interface is present in 07 of the 08 Brazilian regions determined by the Federal Council of Speech and counts with 33 teachers of the total of speech pathologists teachers in Brazil working on this interface. Qualitative results pointed out changes in the concepts of subject and symptom and use of the concept of transference as iconic theoretical-methodological representation of the interface between Speech Therapy and Psychoanalysis. CONCLUSION: It is considered that the speech therapist who works at the interface with Psychoanalysis bases its work on three guiding principles for clinical practice: the concept of subject, symptom and transfer